Hubungan Antara Status Gizi Dengan Kejadian Dismenore Pada Mahasiswi Yang Sedang Mengerjakan Skripsi Di Universitas Muhammadiyah Surakarta - Utari, Nina; , Winarsih Nur Ambarwati, S.Kep., Ns., ETN., M.Kep (2016)
Reproduction health is an important component for women. Reproduction system of women are very susceptible to illness that make complication to her reproduction system. Reproduction system complication on adolescents during menstruation was dysmenorrhea or pain during menstruation.various factors. Risk factors for dysmenorrheal are age < 20 years, smoking, age at menarche, heavy or prolonged menstrual flow, pelvic infection, psychological factor, genetic and nutritional status. Nutritional status are important thing from human health. The bad nutritional status in adolescent caused various abnormality on body function such as reproduction function. The aimed of this study to analyze between nutritional status and dysmenorrhea in students are doing thesis in University Of Muhammadiyah Surakarta. This research was descriptif correlative study conducted on 49 students who end of semester course Nursing Faculty of Health University of Muhammadiyah Surakarta generation 2012/2013 with total sampling technique. Data collection of the research using questionnaires, pair of scales weight, and microtoice. The analyzed using Gamma dan Somers'd correlation test. The result of the analysis Gamma dan Somers'd correlation values -0,176 with p-value 0,097, concluded that no relationship between nutritional status and dysmenorrhea in students are doing minithesis in University Of Muhammadiyah Surakarta. The conclusion of this study are (1)the nutritional status of students are doing minithesis in University of Muhammadiyah Surakarta mostly normal, (2) Dysmenorrhea of students are doing minithesis in University of Muhammadiyah Surakarta who has an experience of dysmenrrhea are rarely, (3) no relationship between nutritional status and dysmenorrhea in students are doing minithesis in University Of Muhammadiyah Surakarta.